Dari Logos ke Hikmah: Mediasi Filsafat Islam dalam Transformasi Rasionalitas Yunani ke Barat - Puspa Fitria Dewi; Muh. Ilham; Natsir Siola (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This article examines the role of Islamic philosophy as an intellectual mediator in the transformation of Greek rationality into the Western philosophical tradition. In dominant philosophical historiography, Islamic philosophy is often reduced to a passive transmitter that merely translated Greek thought into Latin. This article challenges such a reductionist view by arguing that Islamic philosophy functioned as an active epistemological agent that not only inherited but also reconstructed and transformed Greek rationality through the conceptual framework of á¸¥ikmah. Employing a qualitative descriptive approach with historical-philosophical analysis, this study explores the concept of logos in Greek philosophy, the Islamization of rationality by Muslim philosophers such as Al-Kindi, Al-Farabi, and Ibn Sina, and its subsequent influence on Western philosophy through Scholasticism and the Renaissance. The findings demonstrate that Islamic philosophy served as a crucial epistemic bridge that integrated reason and revelation, thereby contributing significantly to the formation of modern Western rationality. This article thus offers a more dialogical and cross-civilizational perspective on the history of philosophy.